ANALISIS FINANCIAL DISTRESS SAAT KRISIS KEUANGAN GLOBAL: STUDI EMPIRIS PADA BUMN NON-KEUANGAN - Nakamura, Tiffany Mica (Media Akuntansi dan Perpajakan Indonesia, 2021)
This study aims to determine the differences and levels of accuracyof the Altman Z-Score, Springate S-Score, and Zmijewski X-Score inpredicting financial distress before, during, and after the global financialcrisis. The sample in this study used nine state-owned companies in thenon-financial sector, which were listed on the Indonesia Stock Exchange forthe period 2005–2012. Data collection used secondary data from thecompany’s annual reports—data analysis methods using the Kruskall - Wallistest as a comparative test used to determine differences. This study indicatesno differences in predictions before, during, and after the global financialcrisis. The accuracy test states that the three prediction models are appropriate,but the Altman Z-Score is the model with the highest accuracy level.